ANALYSIS OF STATISTIC CHARACTERISTICS OF MORPHEMES OF UKRAINIAN LANGUAGE - Bykov, Mykola; Balhovskyy, Dmytro; Kyzmin, Іван (Scientific Works of Vinnytsia National Technical University, 2015)
There had been developed an algorithm and soft ware for the determination of statistic and transitive probability of text morpheme. There had been given the theoretical analysis of the problem of building of efficient hierarchical strategy of text reorganization, and suggested the procedure for building and optimal tree of classification of text images.